PENGEMBANGAN SPIRITUAL RELIGIUS DAN KINERJA PEGAWAI PEMERINTAH KOTAMADYA JAKARTA BARAT - Rosidin Rosidin (Indonesian Journal of Islamic Literature and Muslim Society, 2017)
This study aims to describe the spiritual development of religious employees in the West Jakarta Municipal Government. The focus of the study is the performance of employees after following the spiritual development, as well as the implications of this development for the model of religious spiritual development of employees. This research is a qualitative descriptive research with the approach of Islamic Psychology which combines between reason and faith. With the framework of spiritual intelligence indicator according to Zohar and Marshall modified with atheistic perspective, this research finds that: (1) Spiritual spiritual development of employees carried out by the West Jakarta Municipal Government is done in the framework of the realization of workplace spirituality, which is done through the formation of spiritual culture ) stated in its programs; (2) In general, West Jakarta Municipal Government employees have sufficient performance to provide public services, especially for those who have experienced the process of spiritual development. Nine indicators of spiritual intelligence can be used as a benchmark for their performance, although there are still indicators that have not been fully fulfilled; and (3) The spiritual development of religious employees by the West Jakarta Municipal Government has theoretical implications for the model of religious spiritual development of employees.